Islamic Education and Family Mental Health: A Model of Development of Mental Disorders Patients through a Religious Approach in Paringan Ponorogo - Mahmudin, Afif Syaiful (Didaktika Religia, 2022)
In 2011, the people of Ponorogo were shocked by the news of the "Kampung Gila" in Paringan Jenangan Ponorogo village. The results of a survey conducted by the Malang Mental Hospital and the Ponorogo Regional Government stated that 60 residents suffered from mental disorders. This negative stigma is certainly a heavy burden for the local government and Paringan villagers. Other facts show that people with schizophrenia in Paringan are discriminated against in the form of confinement by their own families and neighborhoods. The problem of mental disorders in Paringan Village has been going on for a long time, but the problem was not immediately addressed. One of the efforts to overcome mental disorders that have been implemented in families in Paringan is through a religious approach. The form begins with a review of medical treatment and rehabilitation that has been obtained by the patient, then it will be used as an important reference in determining the appropriate form of Islamic religious education guidance. The goal to be achieved is to continue and develop coaching in the internal family through parents individually and collectively with psychiatric experts, even by applying a completely new form of religious guidance for sufferers. The coaching strategies used by parents in the family vary greatly, this difference is caused by parenting patterns, the level of understanding and religious practices of very diverse parents, and the character of each sufferer being different from one other. The implications obtained from the guidance of Islamic religious education in the family are the results that sufferers can be independent, not easily emotional and understand the risks of their actions, become calmer and happier and sensitive to their surroundings, no longer harm parents and society, become more productive and of course able to carry out worship obligations diligently with their awareness.